Cardiac Resynchronization Therapy in Heart Failure: Rationale, Results, Indications, Limits and Perspectives - Andrea Mazza; Sergio Valsecchi; Umberto Riva; Maria Grazia Bendini; Massimo Leggio (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Heart Failure is the result of heterogeneous structural heart diseases, especially ischemic disease, and is becoming increasingly common in all Western countries. Many patients continue to be symptomatic in spite of progress in pharmacological therapy, and the risk of mortality remains high in the most advanced functional classes. Cardiac resynchronization therapy can be used as a therapeutic strategy for alleviating symptoms and reducing mortality in selected patients with heart failure. Cardiac resynchronization therapy provides both immediate and medium/long-term results. The immediate results are the reduced QRS duration, the synchrony restoration between the ventricles and between the lateral and septal walls of the left ventricle, the reduced mitral regurgitation and the increased stroke volume. In the medium/long term, left ventricular reverse remodeling occurs and left ventricular ejection fraction is increased. Several trials have documented both increased functional capacity and improvements in quality of life and New York Heart Association class. Moreover, cardiac resynchronization therapy has been seen to reduce HF hospitalizations and mortality and the total number of days of hospitalization. In order to reduce the percentage of non-responders to cardiac resynchronization therapy, it is necessary to optimize the prognostic stratification of candidates for implantation through multi-parameter evaluations and to ensure correct device programming with periodic updates which are widely recommended but not so often performed. Whether indications should be extended will need to be evaluated in view of the known complications mainly associated with lead implantation.